Shifting Identity: An Analysis of Arab States' Passive Response to Israel's Genocide Against Palestinians - Munzilin, Khairul (Journal of Islamic World and Politics, 2026)
Since the end of 2023, the Israeli genocide against the Palestinians in Gaza has attracted the attention of the international community to get involved in stopping this atrocity in various ways. Various responses supporting Palestine come from diverse identities and backgrounds. However, in the midst of the boisterous support for Palestine, the governments of Arab countries around Palestine, with inherent identities that are deeply attached to Palestine, show a stance that tends to be silent and unmoved. This research seeks to answer the related question, ‘Why are Arab countries reluctant and passive in helping the Palestinians under Israeli genocide?’ This question will be elaborated using a constructivist approach and processed with qualitative research methods. This research shows several findings, including: First, despite having a very close identity, the current Arab governments do not show the same level of support as in their previous stance. Second, modern Arab governments increasingly place national interests above collective identity. In general, this paper concludes that the changing priorities of Arab states are due to shifting identity, the degradation of modern Arab identity brought about by the fragmentation of Arab societies along nation-state boundaries.